Neonatal Thermoregulation: A Golden Hour Protocol Update. (August 2021) - Dixon, Kristi Lynn; Carter, Brigit; Harriman, Tiffany; Doles, Bradley; Sitton, Barbara; Thompson, Julie
Abstract : Background: Premature infants are poor regulators of body temperature and are subjected to environmental factors that can lead to rapid heat loss, leaving them vulnerable to an increased risk of morbidity and mortality from hypothermia. Thermoregulation protocols have proven to increase survival in preterm infants. Purpose: To evaluate a Plan-Do-Study-Act (PDSA) cycle on a previously implemented Golden Hour protocol at a military medical care facility for infants born at less than 32 weeks of gestation and weighing less than1500 g. Specific aims included the use of increased delivery/operating room temperatures and proper use of thermoregulatory devices (polyethylene bags and thermal mattress). Methods: Outcomes were analyzed and compared using a pre/postdesign. The data was collected using the neonatal intensive care unit admission worksheet. Results: Although statistical analysis was not significant, clinical significance was illustrated by a decrease in hypothermia rates on admission and at 1 hour of life. There was a 100% compliance rate with increasing delivery room/operating room temperatures and thermal mattress use. Polyethylene bag use compliance was 50%. Implications for Practice: Golden Hour protocols have proven to be an effective tool. Thermoregulation is a significant component of these protocols, and it is imperative that every step is taken to manage the environmental temperature during the birth and admission process. Implications for Research: There is a need for continued research on the impacts of thermoregulatory devices and protocols, with resulting practice and device recommendations.